Morphological Characterization of Functional Brain Imaging by Isosurface Analysis in Parkinson’s Disease. - Castillo-Barnes, Diego; Martínez-Murcia, Francisco J.; Ortiz-García, Andrés; Salas-González, Diego; Ramírez, Javier; Górriz-Sáez, Juan Manuel (World Scientific, 2020)
Finding new biomarkers to model Parkinson’s Disease (PD) is a challenge not only to help discerning between Healthy Control (HC) subjects and patients with potential PD, but also as a way to measure quantitatively the loss of dopaminergic neurons mainly concentrated at substantia nigra. Within this context, the work presented here tries to provide a set of imaging features based on morphological characteristics extracted from I[123]-Ioflupane SPECT scans to discern between HC and PD participants in a balanced set of 386 scans from Parkinson’s Progression Markers Initiative (PPMI) database. These features, obtained from isosurfaces of each scan at different intensity levels, have been classified through the use of classical Machine Learning classifiers such as Support-Vector-Machines (SVM) or Na¨ıve Bayesian and compared with the results obtained using a Multi-Layer Perceptron (MLP). The proposed system, based on a Mann-Whitney-Wilcoxon U-Test for feature selection and the SVM approach, yielded a 97.04% balanced accuracy when the performance was evaluated using a 10-fold cross-validation. This proves the reliability of these biomarkers, especially those related to sphericity, center of mass, number of vertices, 2D-projected perimeter or the 2D-projected eccentricity; among others, but including both internal and external isosurfaces.
Keywords: Parkinson, Enfermedad de - Imágenes; Cerebro - Imágenes; Diagnóstico por imagen; Medicina - Proceso de datos; Diagnóstico - Proceso de datos; Aprendizaje automático (Inteligencia artificial); Parkinson’s Disease; Neuroimaging; Isosurfaces; Parkinson’s Progression Markers Initiative (PPMI); Single Photon Emission Computed Tomography (SPECT); Computer-Aided- Diagnosis (CAD); Supervised learning; Machine learning